The cultural context of education among the Bontoc : a case study / Centro Escolar University - Botengan, Kate Chollipas
This study deals with the relationship between the school and the family in Tocucan, a Bontoc community, as they contribute to the education of its members. Both the school and the family are society's educative agencies directly concerned with the learning by its members of the "proper" values and behaviors not only in the community but also in the bigger society. Learning of such "proper" values and behaviors is important for social order and, therefore, the survival of the group as a human social group.
In partial fulfillment of the requirements for the Degree Doctor of Philosophy
A dissertation presented to the faculty of the Graduate School, Centro Escolar University
Dissertation [Ph.D.] - Centro Eascolar University
Keywords: Education, Rural; Bontoc -- Social life and customs